MENGENAL KARAKTER BANGSA JEPANG MELALUI PERILAKU BAIK YANG INSPIRATIF - Iriyanto Widi Suseno (Diponegoro University, 2017)
The Japanese nation as one of the Asian nations has a unique culture of behavior. This article discusses the character of the Japanese nation through an inspirational aspect of good behavior. In this study using a qualitative descriptive approach, with the historical method factual and eclectic. The results of the study obtained a number of principles of life that medasari behavior of the Japanese who form the character that is; Bushido, Makoto, Genchi, Genbutsu, Hansei, Yū, Jin, Rei, Meiyo. The behavior formed on the basis of the life principle of the Japanese includes; friendly and courteous, expressive, respectful of business or process, growing as a community, procedural, well organized, diligent, and meticulous. A number of Japanese behavior is important to give a lesson for the Indonesian nation when it is currently facing various crises, such as moral kriss, national crises, weakness of race in the homeland and the identity of the nation, and the crisis of independence.